DETERMINATION OF RETARDATION FACTORS FOR ADSORPTION OF CESIUM, COBALT AND STRONTIUM ON THE SOIL OF PINSTECH WASTE DISPOSAL AREA - Iqbal, T.; Rashid, F. (The Nucleus, 2020)
The adsorption of cobalt, cesium and strontium on the soil of PINSTECH radioactive waste disposal area was studied to find the adsorption parameters and retardation factors. Standard batch adsorption experiments were performed for three known concentrations of nitrate solutions of stable nuclides by equilibrating them with soil samples. The treated/equilibrated solution concentrations were measured on adsorption spectrophotometer (Hitachi Model Z8000) equipped with Zeeman background corrector using flame automization mode. Masses adsorbed were calculated by the difference of initial and equilibrated solution concentrations. The adsorption isotherms were obtained by plotting the values of masses of nuclides adsorbed per unit mass of soil versus equilibrium solution concentrations that resulted into straight lines. The Freundlich adsorption parameters were calculated from the slope and intercept of straight lines. The calculated parameters were then used to find the retardation factors at different equilibrium solution concentrations.